Faktor-faktor yang Mempengaruhi Wanita Usia Subur (WUS) dalam Pelaksanaan Deteksi Dini Kanker Serviks Metode IVA Test - Supini, R.; Sajalia, Husniyati; Hardianti (STIKes Hamzar, 2024)
Cancer is the second leading cause of death after cardiovascular disease. In 2019 the death rate of cervical cancer reached 10.1 million deaths in the world. Cervical cancer can be prevented by doing several ways, one of which is IVA which is one method for early detection of cervical cancer using 3-5% acetic acid in the speculo and seen by direct observation. To determine the factors that influence the implementation of early detection of cervical cancer IVA method in the village where the Puskesmas Pengadangan work area is held. This study uses analytical survey method with cross sectional approach. The population is women of childbearing age, the sample number is 90 people with cluster random sampling techniques. The measuring instruments used are questionnaires, and analysis using the chi square test. The level of knowledge of respondents was mostly good as many as 61 people (67.8%), husband support mostly supported as many as 71 people (78.9%), attitudes were mostly positive as many as 67 people (74.4%), and the implementation of early detection of cervical cancer was mostly as many as 76 people (84.4%). The results of statistical tests showed that the level of knowledge obtained p value = 0.000 (<α=0.05), husband support obtained p value = 0.000 (<α=0.05), and attitude obtained p value =0.000 (<α=0.05). There is a relationship between the level of knowledge, husband support, and attitudes towards the implementation of early detection of cervical cancer IVA method.